RELEVANSI UU NO 28 TAHUN 2014 TERHADAP PERLINDUNGAN HUKUM HAK CIPTA LAGU ATAS MARAKNYA COVER LAGU DI PLATFORM DIGITAL - Nurhuda, Dede Yuda Wahyu; Puspita, Marisa; Rosidin, Utang (VARIA HUKUM, 2022)
Abstract The rapid development of digital platforms both as entertainment media requires humans to be more creative in creating new innovations, especially in the field of music. With the development of social media as a medium for entertainment, starting from Tiktok which is currently popular, YouTube, Instagram, and various other media, apart from having a positive impact, it also has a negative impact, such as copyright infringement with the rise of musicians covering songs on social media who do not know ethics. when using other people's songs that have an impact on the use of songs illegally. Copyright is part of intellectual property rights that should be protected, Indonesia itself has regulations on copyright regulation, namely Law No. 28 of 2014. In this study, the author will delve deeper into the relevance of Law No. 28 of 2014 on "protection of song copyright law on the rise of cover songs on digital platforms (social media)â€. The purpose of this research is to find out whether the copyright law no. 28 of 2014 is still relevant or not with current technological developments. The research method used is normative juridical by collecting literary sources, both hard books and digital, such as journals, laws, especially copyright laws.Abstrak Pesatnya perkembangan platfrom digital baik sebagai media hiburan menuntut manusia lebih kreatif dalam menciptakan inovasi baru terutama dalam bidang musik. Dengan berkembangnya media social sebagai media penghibur mulai dari tiktok yang sekarang ini banyak digemari, youtube, Instagram, dan berbagai media lainnya selain memberikan dampak positif pun memberikan dampak negatif, seperti pelanggaran hak cipta dengan maraknya bermunculan musisi cover lagu di media sosial yang tidak tau beretika ketika menggunakan lagu ciptaan orang lain sehingga berdampak pada penggunaan lagu secara illegal. Hak cipta merupakan bagian dari hak kekayaan intelektual yang patut dilindungi, Indonesia sendiri mempunyai regulasi dalam pengaturan hak cipta yaitu UU No 28 Tahun 2014. Pada penelitian ini penulis akan mengulik lebih dalam terkait relevansi UU No 28 Tahun 2014 terhadap â€œperlindungan hukum hak cipta lagu atas maraknya cover lagu di platform digital (media sosial)â€. Tujuan penelitian ini adalah untuk mengetahui apakah UU Hak Cipta No 28 Tahun 2014 masih relevan atau tidak dengan perkembangan teknologi saat ini. Adapun metode penelitian yang digunakan yaitu yuridis normative dengan mengumpulkan sumber-sumber kepustakaan baik hard book maupun digital seperti jurnal, uu khususnya uu hak cipta.